Intergroup contact through online comments : effects of direct and extended contact on outgroup attitudes - Kim, Nuri (2018)
This study contributes to the still limited evidence on the effects of online intergroup contact. We conceptualize online contact as occurring through users’ comments online, an easy and accessible venue for intergroup encounters. We test two forms of online contact: encountering an outgroup member directly (direct online contact) or through an ingroup member (extended online contact) and their effects on outgroup attitudes, here various forms of threat and social distance. We also examine the emotional mechanisms through which these effects emerge. We rely on an online experiment (N = 396) testing online contact with two distinct outgroups, an undocumented immigrant or a gay person. Compared to the control, direct online contact decreased perceived threat and social distance toward gays and lesbians, but not toward undocumented immigrants. Direct online contact improved attitudes toward both outgroups through positive and negative emotions, whereas extended online contact reduced negative emotions, improving attitudes towards undocumented immigrants. We discuss theoretical, methodological and practical implications of these findings.